Aerobic power and anthropometric characteristics of elite basketball referees - Leicht, A. S. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The current study aimed to document the aerobic power and body composition of elite basketball referees. Methods: Prior to the 2000/2001 Mens National Basketball League season, 25 male elite referees completed the Multistage Shuttle run test followed by body composition (body fat%) determination via bioelectrical impedance (BI) (Adult and Athlete modes) and a restricted anthropometric profile. Significant correlations between BI and anthropometric measures were examined via Pearson product correlation coefficients. Pearson: Referees demonstrated a mean (SD) aerobic power of 50.8 (3.2) mL/kgmin and body fat% of 23.8% (8.4%). Body fat% was similar for BI (Adult) and several anthropometric equations. Significant correlations were obtained between BI (Adult) and body fat%, and BI (Adult) and sum of skinfolds. Similar correlations were obtained for BI (Athlete) mode despite a significantly lower body fat%. Regression equations for the prediction of body fat% and sum of skinfolds from BI (Adult) were determined. Conclusion: Elite basketball referees demonstrated significantly greater aerobic power and similar body composition to the general community. In the euhydrated state, BI (Adult) provided a valid measurement of body fat% in elite basketball referees.